The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0042293
|View full text |Cite
|
Sign up to set email alerts
|

Acute Doxorubicin Insult in the Mouse Ovary Is Cell- and Follicle-Type Dependent

Abstract: Primary ovarian insufficiency (POI) is one of the many unintended consequences of chemotherapy faced by the growing number of female cancer survivors. While ovarian repercussions of chemotherapy have long been recognized, the acute insult phase and primary sites of damage are not well-studied, hampering efforts to design effective intervention therapies to protect the ovary. Utilizing doxorubicin (DXR) as a model chemotherapy agent, we defined the acute timeline for drug accumulation, induced DNA damage, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 95 publications
6
47
0
Order By: Relevance
“…Moreover, an apparent increase in the H2AXph139 was also observed in the presence of positive foci in the granulosa cells of the primordial follicles, oocytes from the developing follicles and in the stromal cells post treatment with 0.03µg/mL DXR. On the other hand, Roti et al, () did not observe an increase in the TUNEL and H2AXph139 positive foci in the primordial follicles after 48 hours of treatment in mice treated with 20 mg/kg of DXR. This study indicates that the DNA damage in the primordial follicles is only observed after a long exposure to DXR.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, an apparent increase in the H2AXph139 was also observed in the presence of positive foci in the granulosa cells of the primordial follicles, oocytes from the developing follicles and in the stromal cells post treatment with 0.03µg/mL DXR. On the other hand, Roti et al, () did not observe an increase in the TUNEL and H2AXph139 positive foci in the primordial follicles after 48 hours of treatment in mice treated with 20 mg/kg of DXR. This study indicates that the DNA damage in the primordial follicles is only observed after a long exposure to DXR.…”
Section: Discussionmentioning
confidence: 90%
“…DXR acts by blocking the topoisomerase II action and inducing the production of the reactive oxygen species, which triggers cell death by blocking the protein synthesis and promoting oxidative damage (Tokarska et al, ). Studies in vivo on the DXR action (20 mg/kg) on mice ovary, showed that the accumulation of this drug in the follicles varies with the developmental stage in which the larger follicles (secondary, tertiary and antral) accumulated significantly more doxorubicin than did the smaller follicles (primordial and primary) (Roti et al, ). In the present study it was also observed that the developing preantral follicles cultured with 0.03 µg/mL DXR, had a higher number of foci positive for active caspase‐3 and H2AXph139 compared with those treated with PTX (0.1 or 0.001 µg/mL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIS also increases phosphorylation of components of the PTEN/Akt/FOXO3a pathway that regulates growth activation of primordial follicles (Chang et al 2015, Jang et al 2016. DOX induces DNA damage in somatic cells (Roti Roti et al 2012, Xiao et al 2017. Apoptosis and proliferation of ovarian cortical stromal tissue was affected by drug exposure.…”
Section: Figurementioning
confidence: 99%
“…The exposure of parents to environmental toxicants, such as polycyclic aromatic hydrocarbons (Einaudi et al, 2014;Perrin et al, 2011), Bisphenol A (Goldstone et al, 2015), solvents (Kolstad et al, 1999), metals (Thompson and Bannigan, 2008;Zhou et al, 2016) or various therapies (Bujan et al, 2014;Esquerré-Lamare et al, 2015;Pecou et al, 2009;Roti Roti et al, 2012) may induce DNA damage in male and female germ cells. DNA damage in parental germ cells can lead to reproductive issues, such as reduced fertilization, impaired early embryonic development, a decreased pregnancy rate and increased miscarriage rate (Simon et al, 2014;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%